Comparative Antiatherogenic Effects of Intravenous AAV8- and AAV2-Mediated ApoA-IMilano Gene Transfer in Hypercholesterolemic Mice. (January 2015) - Tian, Fang; Wang, Lai; Arias, Ana; Yang, Mingjie; Sharifi, Behrooz G.; Shah, Prediman K.
Apolipoprotein A-IMilano (ApoA-IM), a naturally occurring Arg173 to Cys mutant of ApoA-I, has been shown to reduce atherosclerosis in animal models and in a small phase 2 human trial. We have shown superior atheroprotective effects of ApoA-IM gene compared with wild-type ApoA-I gene using transplantation of retrovirally transduced bone marrow in ApoA-I/ApoE null mice. In this study, we compared the antiatherogenic efficacy of ApoA-IM gene transfer using Recombinant adeno-associated virus (rAAV) 2 or rAAV8 as vectors in ApoA-I/ApoE null mice. Mice received a single intravenous injection of 1.2 × 10 12 vector genomes of AAV2 or AAV8 vectors expressing ApoA-IM or control empty vectors (12 mice/group). Circulating levels of ApoA-IM were higher in recipients of AAV8 compared with AAV2 at 4, 12, and 20 weeks postinjection. Qualitative polymerase chain reaction analysis of RNA collected from different tissues showed that the AAV8-mediated gene transfer resulted in a more efficient transgene expression in the heart, brain, liver, lung, spleen, and kidney of the recipient mice compared with AAV2. Intravenous AAV8-ApoA-IM injection reduced atherosclerosis in the whole aorta ( P < .01), aortic sinuses ( P < .05), and brachiocephalic arteries ( P < .05) compared with the vector control, whereas there was no statistically significant reduction in atherosclerosis in mice receiving intravenous AAV2-ApoA-IM. The ApoA-IM gene was expressed in the aortic tissue of mice receiving AAV8 ApoA-IM but not in those receiving AAV2 ApoA-IM. Immunostaining showed that compared with the vector control, there was reduced macrophage content in the brachiocephalic ( P < .05) and aortic sinus plaques ( P < .05) of AAV8 ApoA-IM recipients but not in the recipients of AAV2 ApoA-IM. Thus, intravenous injection of AAV8 is more effective than intravenous injection of AAV2 in the expression of ApoA-IM gene. These data provide support for the potential feasibility of this approach for atheroprotection in humans.